Stereoselective Synthesis and Dissolution Studies on Enteric Coated Pellets of (S)-Duloxetine Hydrochloride - Venkatram, Raghunandan; Pai, Vasanth Kumar; Nagaraj, Sriharsha (Journal of Nepal Chemical Society, 2013)
The enantioselective hydrogenation of 2-bromo-1-(thiophen-2-yl)ethanone and further elaboration of thr cyclic carbamate derived from γ-aminoalcohol to provide a facile synthesis of (S)-duloxetine, a potent dual inhibitor of serotonin and norepinephrine reuptake, is described. Enteric coated pellets with polymer load 25% and 30% failed to provide required acid resistant to the pellets but very insignificant amount of drug was leached from the coated tablets in acid phase with polymer load 35% and 40% in the acidic phase whereas almost the whole amount of drug was released in the buffer phase. The results generated in this study showed that proper selection of polymeric materials based on their physicochemical properties as well as polymer load is important in designing delayed release pellets dosage form with acceptable dissolution profile. DOI: http://dx.doi.org/10.3126/jncs.v28i0.8110 Journal of Nepal Chemical Society Vol. 28, 2011 Page:74-79 Uploaded Date: May 24, 2013